DESAIN STRUKTUR DERMAGA MULTIPURPOSE TIPE DECK ON PILE DI PELABUHAN LABUHAN LOMBOK, LOMBOK TIMUR, NUSA TENGGARA BARAT - Indra Abdi Pamungkas, Ovan
Labuhan Lombok Port is a local port located in East Lombok, West Nusa Tenggara, with a multipurpose dock to serve loading-unloading cargo and passengers. Projected of the ship will be increase, so the new dock with the capacity for 2000 DWT of general cargo vessels with deck on pile structure need to be designed. The scope of design in the Final Project includes dock and trestle structure design criteria, environmental data processing, load calculation, determining of structural dimensions, structural modeling analysis, structural reinforcement design, and geotechnical analysis. Analysis of the dock structure is carried out using SAP2000 software. The results of modeling in Unity Check Ratio (UCR), structural deflection, forces in beams and plates, and base reactions. Based on design, the length of dock 101.2 m in width 16.2 m which is connected by two trestles along 40.8 m in width of 5.8 m. The largest UCR is 0.83 for the dock structure and 0.86 for the trestle structure. The depth of piling from seabed is 30 m for the dock and trestel structure.